The Impact of Health Literacy on Surgical Outcomes Following Radical Cystectomy. (1st August 2016) - Scarpato, Kristen R.; Kappa, Stephen F.; Goggins, Kathryn M.; Chang, Sam S.; Smith, Joseph A.; Clark, Peter E.; Penson, David F.; Resnick, Matthew J.; Barocas, Daniel A.; Idrees, Kamran; Kripalani, Sunil; Moses, Kelvin A.
Abstract : Health literacy is the ability to obtain, comprehend, and act on medical information and is an independent predictor of health outcomes in patients with chronic health conditions. However, little has been reported regarding the potential association of health literacy and surgical outcomes. We hypothesized that patient complications after radical cystectomy would be associated with health literacy. In a sample of 368 patients, we found that higher health literacy scores (as determined by the Brief Health Literacy Screen) were associated with decreased odds of developing minor complications (odds ratio = 0.90, 95% confidence interval [0.83, 0.97]). Health literacy should be considered when caring for patients undergoing radical cystectomy and should serve as a potential indicator of the need for additional resources to improve postoperative outcomes.